Robust Speed-Sensorless Vector Control of Doubly Fed Induction Motor Drive Using Sliding Mode Rotor Flux Observer - Djamila Cherifi; Yahia Miloud (International Journal of Applied Power Engineering (IJAPE), 2018)
This paper presents a robust observer for sensorless speed control of doubly fed induction motor (DFIM), based on the slidin mode. In the first step, a model of the doubly fed induction motor fed by two PWM inverters with separate DC bus link is developed. In the second step and in order to provide a robust separate control between flux and motor speed a vector control by field oriented strategy applying a sliding mode regulator was implemented. Finally, speed estimation of a doubly fed induction motor based on sliding mode observer is presented. The simulation tests schow the effectiveness of the proposed method especially in the load disturbances, the change of the refrence speed and low speed. Also the influence of parameter variations will be studied by simulation